Building multi-sided business models for stronger digital agribusiness market development - Chaham, Hamza R.; Bosire, Brian; Ricau, Pierre (Technical Centre for Agricultural and Rural Cooperation, 2018)
Ujuzikilimo soil sensors in Kenya have leveraged soil analysis data acquired from farmers to generate market insights.